2013
DOI: 10.1074/jbc.m112.438762
|View full text |Cite
|
Sign up to set email alerts
|

Seven in Absentia Homolog 2 (Siah2) Protein Is a Regulator of NF-E2-related Factor 2 (Nrf2)*

Abstract: Background: Nrf2 is up-regulated in response to reoxygenation after hypoxia. Results: Hypoxia suppressed Nrf2 expression and induced Siah2 expression. Knockdown of Siah2 rescued hypoxic suppression of an Nrf2 mutant that mimicked phosphorylation at serine 40 or lacked this phosphorylation site. Conclusion: Siah2 serves as a novel regulator of Nrf2. Significance: Association of Siah2 with Nrf2 causes the degradation of Nrf2 irrespective of its phosphorylation status at serine 40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…Recent work has demonstrated that Siah2 protein is a promising therapeutic target in pathological conditions accompanied by a low level of Nrf2 expression [7,40] . The inhibition of Siah2 expression restores the decreased expression of Nrf2-inducible genes and subsequently improves symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work has demonstrated that Siah2 protein is a promising therapeutic target in pathological conditions accompanied by a low level of Nrf2 expression [7,40] . The inhibition of Siah2 expression restores the decreased expression of Nrf2-inducible genes and subsequently improves symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…For example, under hypoxia, Nrf2 is phosphorylated by protein kinase C (PKC), which triggers the release from Keap1. Knockdown of Siah2 rescues hypoxia-induced reduction of both Nrf2 mutants mimicking phosphorylation at Ser40 and lacking this phosphorylation site, suggesting that Siah2 contributes to the degradation of Nrf2 irrespective of its phosphorylation status [7] ( Figure 1). In addition, the knockdown of Siah2, but not Keap1, was shown to significantly attenuate the hypoglycemia-mediated reduction of Nrf2 expression [40] .…”
Section: Baba K Et Al Novel Function Of Siah2 In Ros Metabolismmentioning
confidence: 99%
See 3 more Smart Citations